บทความรับเชิญ การเลี้ยงดูลูกเพื่อเตรียมความพร้อมเข้าสู่ธุรกิจครอบครัว - อภิศักดิ์กุล เอกชัย (Journal of Business Administration The Association of Private Higher Education Institutions of Thailand, 2013)
ปัจจัยสำคัญประการหนึ่งที่มีผลอย่างมากต่อการอยู่รอดของธุรกิจครอบครัวคือ การมีทายาทสืบทอดธุรกิจ ซึ่งแน่นอนว่าทุกครอบครัวอยากให้มีทายาทที่เก่งและมีความสนใจในธุรกิจเข้ามาสืบทอดกิจการของครอบครัว แต่ความสามารถและ ความสนใจในธุรกิจนั้นอาจไม่ได้ถ่ายทอดกันทางสายเลือด จึงเป็นสิ่งจำเป็นที่พ่อแม่ควรต้องเรียนรู้วิธีในการเลี้ยงลูกเพื่อเตรียมความพร้อมในการรับช่วงต่อธุรกิจครอบครัวของตนเองและรับมือในกรณีที่ลูกเลือกที่จะไม่เข้าสู่ธุรกิจครอบครัว ดังนั้นบทความนี้จึงนำเสนอแนวทางในการเตรียมความพร้อมให้ลูกเพื่อเข้าสู่ธุรกิจครอบครัวซึ่งประกอบด้วย (1) แนวทางในการเลี้ยงดูลูก (2) การแสดงบทบาทของพ่อแม่ (3) การชักนำลูกเข้าสู่ธุรกิจ (4) การปฏิบัติต่อการเลือกเส้นทางของลูก (5) แนวทางในการเตรียมความพร้อมให้ลูก RAISING AND PREPARING A CHILD FOR FAMILY’S BUSINESS SUCCESSION The important factor impacting the survival of a family business is to have a decedent to continue the business. Every family certainly prefers to have talented kids who are interested in taking on the family business, however, this cannot be transferred genetically. Thus, parents have to pay attention to the way the kids are raised to prepare them for taking over the family business or in case they decide to do other business. This paper is presenting an approach to prepare children before entering into a family business through (1) ways of raising children (2) roles of parents (3) convincing children into business (4) reaction to children’s career choice, and (5) preparation for children.